Pengaruh Konsentrasi dan Interval Agens Hayati Pseudomonas Fluorescens dalam Menghambat Perkembangan Penyakit Bercak Ungu Tanaman Bawang Merah (Allium ascalonicum L.) - Rudini Rudini; Iin Arsensi; Purwati Purwati (Universitas Widya Gama Mahakam, 2016)
Effect of Concentration and Interval Pseudomonas Fluorescens Biological Agents In Inhibiting the disease Growth purple patches Plants Onion (Allium ascalonicum L). This study aims to determine the effect of concentration and interval administration Pseudomonas fluorescens agents in inhibiting the development of spot disease purple onion crop. This research was conducted in the District of Samarinda Seberang, Samarinda, East Kalimantan using a randomized block design (RBD) with 5 treatments and 3 replications. The first factor is the concentration of Pseodomonas fluorencens with 5 levels: p0 = control, p1 = 5 ml / liter of water / plant, p2 = 10 ml / liter of water / plant, p3 = 15 ml / liter of water / plant, p4 = 20 ml / liter water / plant. While the second factor is the interval Pseodomonas fluorencens with 3 levels: i1 = 1 week, 1 x application until the age of 60 days, i2 = 2 weeks, 1 x application until the age of 60 days, i3 = 3 week 1 x application to the age of 60 days. Observation frequency and intensity showed no symptoms of disease purple spots, results of analysis of variance showed that the Pseudomonas Fluorescens Biological Agents (P) very significant effect on plant height increment 6 WAP. Further significant effect on the number of bulbs and tuber weight. the influence of the interval (I) had no significant effect on plant height parameter 3 WAP, 6 WAP and WAP, number of tillers, tuber number and weight of tubers. Results of analysis of variance showed that the interaction of Pseudomonas Fluorescens Biological Agents and Interval Giving. no real effect on plant height parameter 3 WAP, 6 WAP and 9 WAP, number of tillers, tuber number and weight of tubers.